IMPLEMENTASI CSR SAAT PANDEMIK OLEH PT MULYA MENARA SEJAHTERA SIDOARJO PADA DATA TRANSAKSI PEMBELIAN KREDIT - Dedy Triyono; Feliciana Tjitrohartoko (J-MACC, 2022)
In PT. Mulya Menara Sejahtera there are some problems regarding efficiency in data processing. These problems can certainly be considered not in accordance with the green accounting principles that have been set and are also being a concern during this pandemic. This study aims to analyze and provide recommendations regarding the implementation of CSR during the pandemic by PT. Mulya Menara Sejahtera on their credit purchase transaction data. The research method used is a case study. The results of this study conclude that in PT Mulya Menara Sejahtera, the transaction cycle that occurs manually must be further developed more into digital so that it can better support green accounting efforts in Indonesia and support the limitation of physical interaction during this pandemic. In addition, based on the author's analysis, regarding the transaction cycle that occurs manually, PT Mulya Menara Sejahtera has implemented applicable accounting standards and complied with applicable CSR standards in accordance with Republic of Indonesia’s Law No. 40 of 2007 concerning Limited Liability Companies Article 74.